Structural, chemical, and electrical properties of ZrO2/Ge system formed via oxidation/nitridation in N2O gas ambient - Lei, Zhen Ce; Zainal Abidin, Nor Ishida; Wong, Yew Hoong (Springer, 2018)
The effects of oxidation/nitridation for 15 min at different temperatures (300–800 °C) on metal–oxide–semiconductor characteristics of sputtered Zr thin film based on Ge substrate in N2O ambient have been systematically investigated. The crystallinity of the film were evaluated by X-ray diffraction analysis, Raman analysis, and X-ray photoelectron spectrometer. The crystallite size and microstrain of film were estimated by Williamson–Hall plot analysis. Optical microscope was used to examine samples surface condition and high-resolution transmission electron microscopy was carried out to investigate the cross-sectional morphology. GeO2 was detected in samples with oxidation/nitridation temperature above 700 °C. A possible mechanism of Ge atomic diffusion and its rearrangement in ZrO2 has been proposed and explicated.